KETERAMPILAN KOMUNIKASI PEKERJA SOSIAL DINAS SOSIAL PROVINSI RIAU DALAM PROGRAM KELUARGA HAPARAN PKH DESA KEPAU JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Muhammad Vicky; Rusmadi Awza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The Family of Hope Program (PKH) is a program to provide conditional social assistance to Poor Families (KM). In the PKH KPM program can only be a beneficiary within 5 years after that KPM must resign and be replaced with other poor families. Therefore, social workers should be able to provide guidance on the assistance provided and make it provision after KPM graduates. This study aims to find out how social workers' communication skills in creating contact, capturing or understanding information, providing feedback or feedback, and directing beneficiary families to do something in a hopeful family program (PKH).This research uses qualitative research method with descriptive approach, this research was conducted in Kepau Jaya Village, Siak Hulu District, Kampar Regency. The study subjects consisted of four (4) informants selected through purposive techniques and accidental techniques. Research data obtained through the interview process, observation and documentation. While the data analysis techniques used are data collection by means, data reduction, data presentation and conclusion and verification. To achieve the validity of the data, the author uses the extension of participation and triangulation.The results showed that the communication skills of social workers are the first 4, namely building interpersonal relationships by means of Trust Building and Small talk, the second is capturing and understanding the information of social workers using ways to conform to KPM and not patronizing during communication, then providing feedback with ventilation techniques that are techniques used by social workers to bring to the surface the necessary feelings and attitudes and then use easy language in the KPM , and the last one directed KPM to do something like graduation yaiu to move KPM out of PKH beneficiaries by convincing KPM not to rely and able to utilize PKH assistance and then open a business field to improve KPM ekomoni. Key words: Keterampilan Komunikasi, Pekerja Social, Program PKH